Comparative Analysis of Clinical and Imaging Features of Osteomalacia and Spondyloarthritis - Zhao, Zheng; Chen, Wenji; Wang, Yanyan; Jin, Jingyu; Zhao, Yurong; Zhu, Jian; Huang, Feng (Frontiers in Medicine, 2021)
Aim: To compare the clinical and radiological characteristics of osteomalacia and spondyloarthritis/ankylosing spondylitis (SpA/AS) in order to provide a basis for differential diagnosis. Methods: We carried out a retrospective analysis of patients who were diagnosed with osteomalacia at the First Medical Center of 301 Hospital (Beijing, China) from January 2012 to January 2019. The clinical and radiological data of all patients were collected; at the same time, we selected age- and gender-matched SpA/AS patients for comparison. Results: We enrolled a total of 76 patients, 38 with osteomalacia and 38 with SpA/AS. The mean ages of the two groups were respectively 44.62 14.90 years and 44.85 9.76 years (P > 0.05). Of the osteomalacia patients, 65.79% (n = 25) had previously been misdiagnosed with SpA/AS. In the osteomalacia and SpA/AS groups, there were respectively 31 and 33 patients with low back pain, 22 and 13 patients with peripheral arthralgia, and 13 and 3 patients with heel pain. Alkaline phosphatase (ALP) level was significantly higher in the osteomalacia than in the SpA/AS group (P < 0.05). Serum phosphorus levels, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) levels, and bone mineral density (BMP) were significantly lower in the osteomalacia group than the SpA/AS group (P < 0.05). Twenty-five patients in the osteomalacia group underwent sacroiliac-joint magnetic-resonance imaging (SIJ–MRI); abnormalities were found in ten of these patients, seven of whom met the definition for positive SIJ–MRI according to 2009 Assessment of SpondyloArthritis international Society (ASAS) criteria. All 7 presented with bilateral sacral involvement. Logistic-regression analysis found that the odds ratio (OR) for bone erosion score was 0.551; the higher this score, the lower the possibility of osteomalacia. Conclusion: Clinical and radiological presentations of osteomalacia patients could highly simulate those of spondyloarthritis patients; identifying the differences between these two diseases could effectively decrease the misdiagnosis rate.